2013
DOI: 10.1186/1471-2466-13-49
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for the 6-minute walk test in healthy children and adolescents in Switzerland

Abstract: BackgroundThe six-minute walk test (6MWT) is a simple, low tech, safe and well established, self-paced assessment tool to quantify functional exercise capacity in adults. The definition of normal 6MWT in children is especially demanding since not only parameters like height, weight and ethnical background influence the measurement, but may be as crucial as age and the developmental stage. The aim of this study is establishing reference values for the 6MWT in healthy children and adolescents in Switzerland and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
130
3
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(166 citation statements)
references
References 17 publications
18
130
3
15
Order By: Relevance
“…The results showed that the distance walked by these patients does not vary much with age, height or weight as opposed to what previous studies have shown (Calders, et al, 2008;Casanova et al, 2011;Chetta et al, 2006aChetta et al, , 2006b; P. L. Enright & D. L. Sherrill, 1998a;Klepper & Muir, 2011). 6MWD is affected by height, weight, FEV1, BMI, and less importantly HR at the end of the test (Geiger et al, 2007;Klepper & Muir, 2011;Lammers, Hislop, Flynn, & Haworth, 2008;Albert M. Li, et al, 2007;Oliveira et al, 2013;Ulrich et al, 2013). However, there were no significant differences in 6MWD among IPAH groups regardless of significant differences in height (except between adolescent and adult IPAH groups), weight, BMI, and age.…”
Section: Ipah Groupscontrasting
confidence: 51%
See 1 more Smart Citation
“…The results showed that the distance walked by these patients does not vary much with age, height or weight as opposed to what previous studies have shown (Calders, et al, 2008;Casanova et al, 2011;Chetta et al, 2006aChetta et al, , 2006b; P. L. Enright & D. L. Sherrill, 1998a;Klepper & Muir, 2011). 6MWD is affected by height, weight, FEV1, BMI, and less importantly HR at the end of the test (Geiger et al, 2007;Klepper & Muir, 2011;Lammers, Hislop, Flynn, & Haworth, 2008;Albert M. Li, et al, 2007;Oliveira et al, 2013;Ulrich et al, 2013). However, there were no significant differences in 6MWD among IPAH groups regardless of significant differences in height (except between adolescent and adult IPAH groups), weight, BMI, and age.…”
Section: Ipah Groupscontrasting
confidence: 51%
“…Studies performed in healthy Austrian, Swiss, Chinese, and Turkish children (Geiger, et al, 2007;Albert M. Li, et al, 2007;Ulrich, et al, 2013) were found but no 6MWT studies performed with Spanish children. However in the only study with American children (Klepper & Muir, 2011) demographics are almost identical in age, height, weight and BMI to the control group of the current study.…”
Section: Ipah Children and Healthy Children Groupmentioning
confidence: 99%
“…6MWD is influenced by height, weight, ethnical background, age and developmental stage. There is lack of validity to describe 6MWD in percentage as in adults, it can be interpreted that the influence of age and other growth parameters has a huge influence on 6MWD values in children, as compared to adults (Ulrich et al, 2013). It may also be possible that the normal weight children in our study might have central obesity with high levels of cardio-metabolic risks compared to those without central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies involving field analysis, for evaluation of physical fitness, 6MWT is preferred over other laboratory tests. In our study we had used 6MWD to study their physical fitness because it has following benefits such as walking is one of the normal activities of life reflecting the capacity to do daily activities (Makniet al, 2012), it is simple, easy to administer, it has low cost and can be used in routine (Makni et al, 2012;Kanburoglu, 2014;Roush, 2006;Geiger et al, 2010;Ulrich et al, 2013) validated to have high correlation with workloads, HR, oxygen saturation & dyspnoea responses when compared with standard cycle ergometry& treadmill exercise tests (Makniet al, 2012;Kanburoglu, 2014;Roush, 2006;Ulrich et al, 2013), direct correlation with quality of life which enables an individual to cope against disease process and remain independent (Makniet al, 2012;Ulrich et al, 2013), provides opportunity to evaluate patient in a timely, practical and economical manner (Makniet al, 2012;Ulrich et al, 2013), repeated measurements are possible as the patient has to be evaluated in a disease progression manner (Makniet al, 2012;Geiger et al, 2010;Ulrich et al, 2013) relationships found between 6MWD and crude power and / or HR at which fat oxidation reaches its maximum is the most useful information in targeting the planning of training procedure (Makni et al, 2012;Geiger et al, 2010. However, there are various drawbacks of 6MWD as it may not change with increase in age because of ever-changing hormones and energy levels or discrepancy of inner motivation of children at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…De igual forma, el estudio sobre salud global del año 2012 mostró que el porcentaje de escolares chilenos físicamente activos (60 minutos diarios de ejercicio físico moderado a vigoroso) alcanzaba solo el 15% y 12% en el grupo de 13-15 años y 16-17 años respectivamente (11). La prueba de seis minutos de caminata en niños ha resultado ser una prueba factible de realizar a la población escolar y sus resultados dependerán principalmente de las edades, frecuencia cardiaca postejercicio, altura y peso de los sujetos a evaluar (12).…”
Section: Introductionunclassified